The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1262/jrd.20121
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vitro</i> Assessment of Progesterone and Prostaglandin E<sub>2</sub> Production by the Corpus Luteum in Cattle Following Pharmacological Synchronization of Estrus

Abstract: Abstract.We studied the secretory function of the corpus luteum (CL) in cows following different estrus synchronization protocols. Estrus was synchronized using one (n=4) or two injections (n=5) of prostaglandin F2α (PGF2α; dinoprost), two injections of different analogues of PGF2α (aPGF2α), luprostiol (n=5) and cloprostenol (n=5), at eleven-day intervals, a gestagen implant (norgestomet, n=5, for 10 days) or norgestomet together with a subsequent dinoprost injection on the day of implant removal (n=5). CL sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
0
33
1
4
Order By: Relevance
“…The cows were eliminated by the owners from two dairy cow herds (Experimental Animal Farm of the Polish Academy of Sciences in Baranowo and the Agriculture Farm in Watkowice; Years 2007-2009) because of their low milk production. Estrus was synchronized in the animals by two injections of an analogue of PGF2α (dinoprost, Dinolytic; Upjohn-Pharmacia N.V.S.A., Belgium), as recently described [21]. The onset of estrus was determined by the indicative signs (i.e, vaginal mucus, standing behavior) and was confirmed by a veterinarian by ultrasonographic (USG) examination using a DRAMINSKI ANIMAL Profi Scanner (Draminski Electronics in Agriculture, Olsztyn, Poland) and by per rectum examination.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cows were eliminated by the owners from two dairy cow herds (Experimental Animal Farm of the Polish Academy of Sciences in Baranowo and the Agriculture Farm in Watkowice; Years 2007-2009) because of their low milk production. Estrus was synchronized in the animals by two injections of an analogue of PGF2α (dinoprost, Dinolytic; Upjohn-Pharmacia N.V.S.A., Belgium), as recently described [21]. The onset of estrus was determined by the indicative signs (i.e, vaginal mucus, standing behavior) and was confirmed by a veterinarian by ultrasonographic (USG) examination using a DRAMINSKI ANIMAL Profi Scanner (Draminski Electronics in Agriculture, Olsztyn, Poland) and by per rectum examination.…”
Section: Animalsmentioning
confidence: 99%
“…To study the potential influence of LPA on early pregnancy establishment in the cow (around the time of the highest IFNτ production by the conceptus, just before implantation) in vivo and in vitro studies were carried out on days 15-18 of pregnancy. [21]. The onset of estrus was determined by the indicative signs (i.e, vaginal mucus, standing behavior) and was confirmed by a veterinarian by ultrasonographic (USG) examination using a DRAMINSKI ANIMAL Profi Scanner (Draminski Electronics in Agriculture, Olsztyn, Poland) and by per rectum examination.…”
mentioning
confidence: 99%
“…On the other hand, large arteriolovenous vessels remained intact and exhibited a thickening wall in the regressing CL, suggesting that arteriolovenous vessels may have a role in the expeditious disrupture of the bovine CL. Further studies will be needed to clarify the physiological meaning for the increase in arteriolovenous blood vessels in the regressing CL.It is well considered that spontaneous luteolysis induced by endogenous PGF2α and pharmacological luteolysis induced by administration of exogenous PGF2α are different [28][29][30]. In fact, Skarzynski et al recently reported that estrus synchronization, depending on the method and PGF2α analogue, may induce lower P production and decrease the sensitivity of the CL to luteotropic factors compared with those in the spontaneous estrous cycle in the cow [30].…”
mentioning
confidence: 99%
“…The animals were eliminated by the owner from two dairy cow herds (Years 2004(Years -2006) because of their low milk production. Estrus was synchronized in the cows using double injections of an analogue of PGF2α (dinoprost, Dinolytic; Pharmacia & Upjohn N.V.S.A., Belgium), as described recently by Skarzynski et al [35] for estrus synchronization of multiparous cows. The onset of estrus was determined by observing the signs of estrus (i.e., vaginal mucus, standing behavior) and was confirmed by a veterinarian via ultrasonography (USG) examination using DRAMINSKI Animal profi Scanner (Draminski Electronics in Agriculture, Olsztyn, Poland; www.draminski.com) and per rectum examination.…”
mentioning
confidence: 99%